Statystyczne metody badania przestrzennej dyspersji cen produktów rolnych - Machyńska, Irena; Stelmaszewski, Andrzej (Wydział Prawa i Administracji UAM, 1969)
The authors divide the literature of the subject in three groups: 1: the empirical- analytical papers that represent the phenomena and factors that caused them in relation to the concrete, territorial structure of prices; 2. the literature that deals with problems of the methods of researches of dispersion of prices in space; 3. the literature dealing with the methodology of the regional indexes of prices. In general the methods of examinations of the dispersion of prices in space can be devided in two groups: static and dynamic. Among the static ones we can differentiate 3 important subgroups: cartographic methods, methods based on purposefully choosen characteristic bigness and the method based on the measures of dispersion. Among the methods based on purposefully choosen characteristic bigness, the author numbers: mean local prices, absolute and relative deflections of the local price from the level of the conventionally price accepted as a base and the coefficients of the frequency of changes. Among the methods based on the measures of dispersion the authors individualized these in which are used: the area of the changes of local prices, the standard deflection, the mean coefficient of frequency, relations of the chain factors and the deflection from trend. The dynamic methods are limited by the authors to the characteristic of the regional indexes of prices.
Spatial Dispersion of Prices of Agricultural Products and Statistical Methods of their Examination